Book Review: Olena Fialko, Amazons: Myths and Reality, 2023. Kyiv: Institute of Archaeology of the National Academy of Sciences of Ukraine, 434 p., ill. [in Ukrainian: Олена Фіалко, Амазонки: міф або реальність, Київ: Інститут археології Національної академії наук України, 2023, 434 с., іл.], ISBN 978-617-7810-35-2 - Evelina Kravchenko (Archaeologia Polona)
The Institute of Archaeology of the National Academy of Sciences of Ukraine has published Olena Fialko’s book Amazons: Myths and Reality. Actually, it is a publication of the author’s thesis for the degree of Doctor of Historical Sciences, which she successfully defended in 2020 at the Institute in Kyiv.